Islamic Republic of Mauritania : Technical Assistance Report-Report on the External Sector Statistics Technical Assistance Mission (March 19-30, 2018). (IMF Staff Country Reports; Country Report ;, 2019)
With the support of the IMF's Middle East and Central Asia Department (MCD), and at the request of the Central Bank of Mauritania (BCM), the IMF's Statistics Department (STA) mission visited Nouakchott from March 19-30, 2018, to provide technical assistance (TA) in the area of external sector statistics (ESS). This mission is part of an initiative financed by the Financial Sector Stability Fund (FSSF): Balance Sheet Approach (BSA) Sub-Module. This intersectoral effort will enable the production of more reliable BSA matrices to support macroprudential policies, the country's financial stability analysis, and the IMF's surveillance missions. The mission's key objectives were to work closely with the BCM in order to (i) improve the compilation of the balance of payments (BOP), and (ii) propose a framework for compiling the international investment position (IIP). Based on the findings and recommendations of the last TA mission on external sector statistics (ESS) carried out at the BCM in October 2016, this mission notes the need to improve the quality of most items in the BOP, particularly the financial account, which could also aid IIP compilation efforts in the near future.